Documents from 1551-1879 Archivo General de Indias Arquivo Histórico de Moçambique Biblioteca Histórica de la Universidad Complutense de Madrid Biblioteca Nacional de España Instituto de Valencia de Don Juan Lily Library Real Academia de la Historia : Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro (Georg Olms Verlag, 2023)
Keywords: Relations – Oman – Portugal

Documents from 1551-1827 Archivo General de Indias Arquivo Histórico de Moçambique Biblioteca Histórica de la Universidad Complutense de Madrid Biblioteca Nacional de España Instituto de Valencia de Don Juan Lily Library Real Academia de la Historia : Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro (Georg Olms Verlag, 2023)
Keywords: Relations – Oman – Portugal

Documents from 1817-1877 Arquivo Histórico Ultramarino : Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro (Georg Olms Verlag, 2023)
Keywords: Relations – Oman – Portugal

Documents from 1729-1817 Arquivo Histórico Ultramarino : Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro (Georg Olms Verlag, 2023)
Keywords: Relations – Oman – Portugal

Étude de cas de l'attractivite insulaire: l'ile de Corse et de Djerba - Ksouri, Rabii; Abdennadher, Imen (Researchgate, 2024)
L'article aborde le sujet de l'attractivité territoriale des îles, en se concentrant particulièrement sur les îles de Corse et de Djerba. L'article utilise la méthodologie prospective et l'analyse structurelle, en mettant en œuvre la méthode Matrice des Impacts Croisés (MICMAC), pour identifier les principaux facteurs d'attractivité territoriale. Deux groupes d'investisseurs (un pour Djerba et un pour la Corse) sont interrogés pour recueillir des données qualitatives et quantitatives. Les résultats et interprétations sont basés sur l'analyse des cartographies générées par le logiciel MICMAC. La typologie des variables est analysée, et des schémas de relations entre les variables d'attractivité territoriale sont présentés pour les investisseurs de Djerba et de Corse. L'article souligne l'importance de l'attractivité territoriale pour le développement des îles, et met en évidence les différences dans la perception de cette attractivité entre les investisseurs de Djerba et de Corse. Il propose un modèle conceptuel basé sur les résultats de l'analyse structurelle, mettant en lumière les facteurs clés d'attractivité pour chaque territoire
Keywords: Tourisme – Djerba

Stability state of a Mediterranean coastal environment threatened by erosion: the case of the Djerba Island (Gulf of Gabes, SE-Tunisia) - Saïdi, Hanen; Jhine, Meyessa; Bjaoui, Béchir (2023)
The Djerba Island (Gulf of Gabes, SE-Tunisia) that is part of the South Rive of the Mediterranean is classified lately as an international heritage site. Despite this, it suffers from erosion. So, it's necessary to study and monitor its stability state (erosion/accretion) to predict future erosion. In the present work, the stability state was determined by studying the coastline evolution using photographs (1991) and satellite images treated by Remote Sensing and GIS tools. Extracted coastlines (schematized by polylines or extracted by the calculation of MNDWI index) have been superimposed. Their evolution (distances and rates) was calculated automatically using the Arc GIS Digital Shoreline Analysis System extension. Results show accelerated erosion over the last period 2016–2020 for all cells on the Island. The evolution over a period of 45 years, from 1975 to 2020, shows a coastline retreat along the entire Island (3 to 10 m/year), with the exception of the sandy spits of Ras Rmal and Borj Kastel (accretion due to the contributions of sediments by coastal drift currents). The sea level rise and the various hydrodynamic and anthropogenic forcings have led to this state instability and this generalized erosion.